Application of Guano Filtrate on Infection of Pepper yellow leaf curl virus in Chilli Plants - Nada, Azmi Khoirin; Hidayat, Sri Hendrastuti (Jurnal Fitopatologi Indonesia, 2020)
Application of Guano Filtrate on Infection of Pepper yellow leaf curl virus in Chilli Plants Pepper yellow leaf curl virus (PYLCV) is a member of Begomovirus genus, which causes yellow leaf curl disease in chili plants in Indonesia. This virus is transmitted by vector Bemisia tabaci (Hemiptera: Aleyrodidae). Research was carried out to determine the potential of guano in suppressing yellow leaf curl disease in chili pepper. Field experiment was conducted using factorial design in a randomized block design with 2 factors. The first factor was chili cultivar (‘Gelora’, ‘Bara’, and ‘Pelita 8’) and the second factor was treatment of guano filtrate (before virus inoculation, 1 week after virus inoculation, 2 weeks after virus inoculation, virus inoculation without guano, without virus inoculation nor guano). Virus inoculation was carried out using B. tabaci. In general, symptoms were developed 1 to 3 weeks after inoculation although the incubation period varied between chili cultivars. Green mosaic with leaf curling was mostly found in ‘Gelora’, whereas yellowing with leaf cupping was mostly found in ‘Bara’ and ‘Pelita 8’. Begomovirus infection on plant showing symptoms has been confirmed by polymerase chain reaction method. Application of guano did not cause suppression on disease incidence and severity. Similarly, it did not affect plant height and flowering period.